Layered cathode structure based on alternate distribution of functional layers and buffer layers and rapid trial-manufacturing method thereof

By adopting a structure with alternating distribution of functional layer-buffer layers in the layered cathode, using thermochemical materials and nanocrystalline materials with high plastic deformation capabilities, the problem of cracking and falling off of the layered composite electrode during arc discharge is solved, and higher ablation uniformity and cathode life are achieved.

CN119673727AActive Publication Date: 2025-03-21SHENYANG AIRCRAFT CORP

Patent Information

Application Number
CN202411745592.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing layered composite electrodes are prone to cracking, splitting and falling off the reinforcement layer during arc discharge, resulting in early failure of the cathode and difficulty in taking into account the electrode life extension and quality improvement of discharge processing.

Method used

A layered cathode structure is adopted in which the functional layer-buffer layer is alternately distributed. The functional structure layer is composed of several sub-functional layers and buffer layers, and is alternately stacked between layers and metallurgically combined at the interface. The sub-functional layer is made of thermochemical materials, and the buffer layer is made of nanocrystalline materials with high plastic deformation capability, forming a multi-layer composite structure through cyclic alternating deposition and post-treatment processing.

Benefits of technology

It effectively solves the cracking, splitting and coating peeling problems caused by plasma discharge severity heat and quenching in application scenarios such as electro-spark processing hole making and arc welding, which improves ablation uniformity and ablation resistance, extends the cathode life and improves processing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673727A_ABST
    Figure CN119673727A_ABST
Patent Text Reader

Abstract

The invention relates to a layered cathode structure based on functional layer-buffer layer alternate distribution and a rapid trial-manufacturing method thereof, and belongs to the technical field of machining, the layered cathode structure comprises a functional structure surface layer and a matrix, and the functional structure surface layer is further formed by stacking and alternately arranging a plurality of sub functional layers and buffer layers. In actual service, a refractory oxide layer is generated in situ on the basis of the functional layer made of the thermochemical material, self-protection is completed, and electrons are emitted to support arc discharge; and the buffer layer is made of a nanocrystalline material with high plastic deformation capacity, so that the thermal stress of the functional layer can be released through proper deformation of the buffer layer, and meanwhile, cathode spot migration can be accelerated when the buffer layer is in contact with a cathode arc so as to slow down cathode burning loss. Through the synergistic effect of the functional layer and the buffer layer, the problems of cracking, splitting and coating falling caused by plasma discharge shock heating and shock cooling of the layered cathode in application scenes such as electric spark machining hole making and electric arc welding are solved, meanwhile, the ablation uniformity is improved, and the ablation rate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a layered cathode structure based on alternating distribution of a functional layer and a buffer layer and a rapid trial production method thereof, and belongs to the technical field of mechanical processing. Background Art

[0002] Electrode ablation is an inevitable failure process of metal electrodes during their service. During arc discharge, arc plasma continues to burn between the cathode and the anode. The potential difference distribution between the cathode-arc column region and the anode is non-uniform, and can be divided into the cathode potential drop region, the arc column region and the anode potential drop region. In contrast, the potential change in the near-cathode region is particularly drastic, giving the positively charged particles reaching the cathode surface a larger average energy. Correspondingly, the cathode arc ablation is more intense. In addition, when the metal cathode discharges, it is easy to be concentratedly ablated by the cathode spot, which then forms an ablation pit deep inside, causing non-uniform arc ablation and even abnormal cathode perforation failure. Cathode spotting is a characteristic behavior of metal cathode discharge, and the current density at the bottom of the spot can reach 10 4 ~10 8 A / cm 2 As mentioned above, under extremely high spot current density and heat flux density, the cathode material is burned in the form of melting, oxidation, boiling and splashing. Cathode surface strengthening is an effective means to improve the uniformity of metal cathode discharge ablation and reduce the ablation rate. Its principle is to produce a strengthening layer on the surface of the original cathode substrate through surface strengthening methods such as vapor deposition, laser cladding, and additive manufacturing, and use the strengthening layer to replace the substrate to emit electrons to support the arc, thereby decoupling the different performance requirements of the cathode surface and the substrate. However, under the intense heat input of the arc plasma arc root, the sudden heating and cooling of the cathode surface is easy to cause concentrated thermal stress. When the thermal expansion properties of the strengthening layer and the metal matrix are very different, the strengthening layer is often deformed, cracked, or even peeled off as a whole, exposing the metal matrix directly to the arc arc root, causing the surface-strengthened cathode to fail prematurely. Therefore, it is urgent to develop a new layered composite cathode structure that is resistant to cracking and its rapid trial production technology.

[0003] At present, hafnium and zirconium thermochemical materials are suitable for the surface strengthening layer of copper electrodes. During discharge, on the one hand, they use their own low electron work function to ensure sufficient electron emission to support the stable burning of the arc, and on the other hand, they react in situ to generate a refractory oxide layer to protect the substrate. In view of the cracking problem caused by the difference in thermal expansion between the hafnium and zirconium strengthening layers and the copper substrate, the main solutions are to add an intermediate transition layer, reduce the thickness of the strengthening layer, and adjust the arc discharge parameters. Studies have shown that adding a certain thickness of 50% Zr + 50% Cu gradient layer between the zirconium strengthening layer and the copper substrate can inhibit cracking to a certain extent, and only local cracks appear in the Zr / Cu layered electrode after discharge. After further replacing the intermediate layer material with Nb, the layered electrode has a complete structure after arc discharge. The principle of reducing the thickness of the strengthening layer to inhibit cathode cracking is to coordinate the deformation of the surface strengthening layer by utilizing the overall deformation capacity of the substrate. The specific implementation methods of arc discharge parameter regulation to inhibit cracking include reducing arc current, setting gradient current / voltage and extending arc dwell time, etc. The core is to reduce the cooling rate of the cathode surface molten pool. Taking the EDM process with an arc current of 100A as an example, compared with direct arc ignition, the preset gradient increasing current value of 25A-50A-75A-100A can alleviate the peeling of the strengthening layer caused by high current discharge.

[0004] However, the existing anti-cracking solutions for layered composite electrodes are difficult to take into account both electrode life extension and EDM quality and efficiency improvement. Although the introduction of an intermediate layer can inhibit brittle intermetallic compounds and release stress, it is necessary to screen the intermediate layer in combination with the specific electrode material system. At the same time, laser cladding to prepare the strengthening layer and the intermediate layer often requires secondary exploration of the preparation process, and it is impossible to avoid the violent ablation process when the strengthening layer burns out and the matrix is ​​exposed. Reducing the thickness of the strengthening layer on the surface of the layered electrode will shorten the service life of a single cathode and increase the number of electrodes consumed in the electromachining process. Similarly, reducing the arc current or setting the gradient current / voltage will increase the time required for a single electromachining, and changing the current and voltage parameters will easily induce the appearance of deformed structures such as a deformed remelting layer on the workpiece surface. Therefore, the existing anti-cracking design scheme for layered composite electrodes cannot simultaneously improve the service performance of the electrode and achieve EDM quality and efficiency improvement. Summary of the invention

[0005] The purpose of the present invention is to provide a layered cathode structure based on the alternating distribution of functional layers and buffer layers and a rapid trial production method thereof. The layered cathode structure of this scheme can effectively solve the problems of cracking, splitting and shedding of the strengthening layer during the service of layered cathode arc discharge. The layered cathode structure specifically comprises a functional structure layer and a substrate, wherein the surface layer of the functional structure is further composed of several layers of sub-functional layers and a buffer layer, and the layers are alternately stacked and metallurgically bonded at the interface. The synergistic effect of the sub-functional layer and the buffer layer is utilized to solve the problems of cracking, splitting and coating shedding caused by the sudden heating and cooling of plasma discharge in the application scenarios of electrospark machining and arc welding, while improving the uniformity of ablation and reducing the ablation rate, thereby achieving cathode life extension and processing efficiency improvement.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] Based on the layered cathode structure with alternating functional layer and buffer layer and its rapid trial production method, several layers of sub-functional layers and buffer layers are tightly stacked on the surface of the cathode substrate. When in actual service, the sub-functional layer made of thermochemical materials discharges in situ to generate a refractory oxide layer to protect the substrate, while densely emitting electrons to support arc discharge; correspondingly, the buffer layer is made of nanocrystalline material with high plastic deformation ability, which can release the thermal stress generated by the discharge process of the sub-functional layer through its own moderate deformation, and accelerate the migration of cathode spots to slow down cathode burning when in contact with the cathode arc. The specific steps of the rapid trial production technology involving layered cathode structures are: cathode material design-base material deposition-surface roller grain gradient-cyclic alternating deposition-post-processing.

[0008] The invention discloses a layered cathode structure based on alternating distribution of functional layer and buffer layer and a rapid trial production method thereof, comprising the following steps:

[0009] Step 1: Cathode material and configuration design. According to the environmental characteristics of the cathode during its specific service life and in accordance with the design criteria for dedicated electrode materials, select appropriate sub-functional layers and buffer layer materials. Design the layer thickness and number of layers of the multi-layer composite structure with reference to the arc current and time of a single EDM. Determine the preparation method of the multi-layer structure based on the material type and structural characteristics.

[0010] Step 2: Deposition of substrate materials. Metals A and B represent the sub-functional layers and buffer layer materials of the layered electrode. On the surface of the conductive electrode substrate, the first layer A is melt-deposited based on reasonable manufacturing technology. The key control values ​​of the deposition process are layer thickness, surface and internal forming quality.

[0011] Step 3: Grain gradient of surface layer by rolling. Based on the first layer A, the surface layer is pressed down by unidirectional rolling, so that the near-surface layer is deformed into a nanocrystalline and submicron crystalline deformation layer. After rolling, the grain size in the deformation layer gradually increases from the nanometer level to the micron level in the vertical direction downward, showing a gradient distribution of grain size, thereby achieving the surface grain gradient of the buffer layer material.

[0012] Step 4: Cyclic alternating deposition. Based on the layer A after roller pressing, adjust the parameter combination to perform secondary deposition manufacturing of the surface sub-functional layer B, and also focus on controlling the layer thickness and surface / internal forming quality. Then, according to the number of layers contained in the specific electrode structure, iterate steps 2 to 4 for multiple times to perform alternating deposition of layer A and layer B. Finally, after several cycles, a functional layer-matrix layered composite electrode blank is made, and the functional layer includes a preset stacked distribution sub-functional layer-buffer layer.

[0013] Step 5: Post-processing: For the layered composite electrode blank prepared in steps 1 to 4, the outer peripheral wall and the upper surface are finely processed by CNC machining or other methods to remove surface defects such as burrs and spheroidized particles to ensure that the surface to be discharged is flat and smooth.

[0014] Furthermore, the electrode material design criteria involved in the cathode material design stage specifically revolve around sub-functional layer materials and buffer layer materials. The sub-functional layer should have the following basic physical and chemical properties: 1) Thermochemical discharge properties, its own work function is lower than 4.2eV, and at the same time, after discharge in air atmosphere, a conductive refractory oxide layer can be formed on the surface, and the oxide layer has stable performance and a higher melting point than pure metal; 2) The melting point is higher than the melting point of the matrix material; 3) It has a certain plastic deformation ability. The buffer layer should have the following basic physical and chemical properties: 1) The plastic deformation ability is higher than that of the sub-functional layer material; 2) Its own work function is not higher than 4.6eV; 3) When the linear expansion coefficient of the matrix is ​​X, the thermal expansion coefficient of the buffer layer is between 0.8X and 1.2X.

[0015] Furthermore, the functional layer involved in the layered cathode includes several sub-functional layers and a buffer layer, presenting a multi-layer stacking structure, the thickness of a single layer should be between 1 and 3 mm, and the thickness of the overall functional layer should not exceed 20 mm. In this way, the concentrated thermal stress of the functional layer during arc discharge is released layer by layer, and the deformation mismatch caused by the mismatch between the thermal expansion properties of the functional layer and the substrate is alleviated.

[0016] Furthermore, in the deposition process of the base material, in order to ensure the interface bonding performance between the buffer layer and the substrate, priority should be given to the use of strong interface metallurgy combined with metal melting deposition technology such as laser fuse deposition and high-speed laser cladding. At the same time, in order to meet the design requirements for single layer thickness and internal micron-level grain size in the structural design stage, a combination of high scanning rate and high laser power parameters should be adopted in the deposition manufacturing process to increase the cooling rate of the molten pool and promote grain refinement.

[0017] Furthermore, the buffer layer surface is subjected to a rolling grain gradient treatment, which is implemented by facilitating a unidirectional rolling process to form a gradient grain size change from nanocrystalline to microcrystalline on the upper surface of the buffer layer. After processing, the upper surface of the buffer layer is nanocrystalline, and the grain size gradually increases from the surface to the micron scale.

[0018] Furthermore, the cyclic alternating deposition of the sub-functional layer and the buffer layer has the characteristics of being fast and having a large design domain. Taking high-speed laser cladding deposition forming as an example, when two or more metal powder raw materials are fed into the module, by placing powder A and powder B into the feeding module 1 and 2 respectively, when the present invention involves alternating deposition of two materials, heterogeneous materials can be quickly and flexibly prepared by switching modules.

[0019] Furthermore, the anti-cracking property of the layered cathode structure with alternating functional layers and buffer layers is achieved through the design of a multi-metal layer stacking structure. The sub-functional layer directly faces the arc root, and it will be difficult to avoid thermal stress during service. At this time, the buffer layer on the back will support the deformation of the sub-functional layer with a strong plastic deformation ability, thereby partially releasing the stress. After multiple sub-functional layers and buffer layers are compounded, the thermal stress of discharge ablation can be released to the greatest extent, deformation can be alleviated, and interlayer cracking can be inhibited.

[0020] Furthermore, the functional layer-buffer layer layered cathode structure has high uniformity and ablation resistance in the discharge ablation process. When the arc discharge continues, the sub-functional layer reacts in situ to generate a refractory oxide layer, which protects the substrate and reduces the ablation rate, while promoting the formation of type 1 cathode spots to improve ablation uniformity. When the single-layer functional layer is burned out, the buffer layer directly faces the arc root, and the surface nanocrystals can accelerate the migration of cathode spots, reduce the residence time of the spots, and reduce the heat flux density on the cathode surface. Based on the system mechanism of the sub-functional layer and the buffer layer, the cathode's anti-cracking characteristics and ablation resistance and long life characteristics are simultaneously promoted.

[0021] Compared with the existing layered cathode, the present invention has the following advantages:

[0022] 1) Applicable to a wide range of cathode structures and sizes. The functional layer-buffer layer stacking design is used to achieve crack resistance, and the thermal stress of the service process is fully released based on the material level and structural level. This multi-layer electrode structure is suitable for both thin-walled cylindrical arc heater cathodes and rod-shaped EDM hole-making electrodes, and can be flexibly migrated to a variety of structures and sizes.

[0023] 2) The cathode has excellent ablation resistance throughout its life cycle. When the layered cathode is discharged and in service, the functional layer reacts in situ to generate a refractory oxide layer to protect the substrate and reduce the ablation rate, while promoting Class 1 spots with a slight degree of ablation. When the sub-functional layer is burned and the buffer layer is discharged, the nanocrystalline surface accelerates the migration of cathode spots and reduces the input heat flux. Both the functional layer and the buffer layer can improve the cathode's ablation resistance and ensure full life cycle service performance.

[0024] 3) The cathode has a high achievement rate of designed life. Most existing layered cathodes have excellent ablation performance under short-term, low-current discharge conditions, but are prone to cracking and premature failure after long-term service and heat accumulation, and the life achievement rate is limited. The layered cathode involved in the present invention relies on a multi-layer structure of alternating soft and hard stacking to effectively improve the achievement rate of the cathode's designed life and avoid abnormal failure before reaching the theoretical life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1(a) is a schematic diagram of a layered cathode structure with alternating functional layers and buffer layers;

[0026] Figure 1(b) is a schematic diagram of the working process of the layered electrode;

[0027] FIG1( c ) is a schematic diagram showing the buffer layer as a carrier of the arc root;

[0028] Figure 2 A diagram showing the preparation process of a layered cathode with alternating functional layers and buffer layers;

[0029] Figure 3(a) is a schematic diagram of a structure with uniform thickness of the functional layer and the buffer layer;

[0030] Figure 3(b) is a schematic diagram of increasing the thickness of the sub-functional layer;

[0031] Figure 3(c) is a schematic diagram of increasing the thickness of the buffer layer;

[0032] Figure 4 This is the anti-cracking mechanism diagram of the layered cathode arc discharge section;

[0033] Figure 5 This is a scanning electron micrograph of the layered cathode burnt surface;

[0034] Figure 6 (a) shows the morphology of the layered cathode (a) prepared by only the control process;

[0035] Figure 6(b) shows the cross-sectional morphology of the layered cathode prepared using only the control process.

[0036] In the figure: 1-functional structural layer, 2-substrate, 3-subfunctional layer, 4-buffer layer, 5-arc plasma, 6-anode, 7-layered cathode, 8-refractory oxide layer, 9-cathode spot, 10-raw material feeding module, 11-processing roller. DETAILED DESCRIPTION

[0037] Figure 1 is a schematic diagram of the new layered cathode structure and discharge. Figure 2 Figure 3 is a diagram of the preparation process of a layered cathode with alternating functional layers and buffer layers. Figure 4 shows various layered cathode structure design schemes. Figure 4 This is the anti-cracking mechanism diagram of the layered cathode arc discharge section. Figure 5Figure 6 is a scanning electron micrograph of the burned surface of the layered cathode. Figure 7 is a surface morphology (a) and cross-sectional morphology (b) of the layered cathode prepared by only the control process.

[0038] The present invention relates to a layered cathode structure with alternating functional layers and buffer layers, such as Figure 1a As shown, it specifically comprises a functional structure layer (1) and a substrate (2), wherein the functional structure surface layer is further composed of several layers of sub-functional layers (3) and a buffer layer (4), and the layers are alternately stacked and metallurgically bonded at the interface. In actual service, it can significantly solve the cracking and functional layer detachment problems of conventional layered cathodes, and has the advantages of 1) being applicable to a wide range of cathode structures and sizes; 2) having excellent ablation resistance throughout the entire life cycle; and 3) having a high design life achievement rate.

[0039] During the operation of the layered electrode, the arc plasma (5) burns between the anode (6) and the layered cathode (7), and the sub-functional layer made of thermochemical material discharges in situ to generate a refractory oxide layer (8) to resist arc root ablation, such as Figure 1b As shown, the substrate is protected to extend the cathode life, while the non-metallic oxide layer promotes the high-speed migration of cathode spots, making the cathode surface uniformly ablated. Correspondingly, when the electrode continues to discharge until the surface sub-functional layer is burned, the buffer layer becomes the carrier of the arc root, as shown in Figure 1c As shown. The buffer layer is made of nanocrystalline material with high plastic deformation ability, which can release the thermal stress generated by the discharge process of the sub-functional layer by its own moderate deformation, and can accelerate the migration of cathode spots to slow down cathode burning when contacting the cathode arc. The numerous cathode spots (9) on the cathode surface migrate at high speed in the discharge area to disperse the arc root of the cathode arc.

[0040] The corresponding layered cathode structure with alternating functional layers and buffer layers is prepared as follows Figure 2 As shown, it mainly includes the following series of steps: 1) cathode material and configuration design; 2) substrate material deposition; 3) surface rolling grain gradient; 4) cyclic alternating deposition; 5) post-processing.

[0041] Cathode material and configuration design. Figure 2As shown in a, the layered electrode structure is alternately stacked by sub-functional layer A and buffer layer B. In the cathode material and structure design stage, the material type (A1, A2, B1, B2...) and structural characteristics (thickness α, number of layers β) need to be designed. The sub-functional layer should have the following physical and chemical properties: 1) Thermochemical discharge properties, its own work function is lower than 4.2eV, and the oxide layer is refractory, stable and has a higher melting point than pure metal; 2) The melting point is higher than the melting point of the matrix material; 3) It has a certain plastic deformation ability. The buffer layer should have the following physical and chemical properties: 1) The plastic deformation ability is higher than that of the sub-functional layer material; 2) The own work function is not higher than 4.6eV; 3) When the linear expansion coefficient of the matrix is ​​X, the thermal expansion coefficient of the buffer layer is between 0.8X and 1.2X. Referring to the arc current and time of a single discharge machining, the layer thickness and number of layers of the multi-layer composite structure are designed, where the single layer thickness should be between 1 and 3mm, and the overall functional layer thickness should be less than 20mm.

[0042] Deposition of substrate material. On the surface of the conductive substrate, the first layer A is melt-deposited based on reasonable manufacturing technology. The key control values ​​of the deposition process are layer thickness, surface and internal forming quality. Taking high-speed laser cladding deposition as an example, Figure 2 As shown in b, the manufacturing process adopts a combination of high scanning rate and high laser power parameters to increase the cooling rate of the molten pool and promote grain refinement. In order to facilitate the subsequent alternating cladding process to be carried out efficiently, a deposition device containing two raw material feeding modules (10) is adopted, and raw materials A and B of the sub-functional layer and the buffer layer are respectively loaded into the two feeding modules, and the heterogeneous materials are quickly and flexibly prepared by switching the modules.

[0043] Grain gradient of surface layer rolling. Based on the first layer A, the surface layer is pressed down by unidirectional rolling, so that the near-surface layer is deformed into a nanocrystalline and submicron crystalline deformation layer, such as Figure 2 c. After the rolling process (11), the grain size in the deformed layer gradually increases from the nanometer level to the micrometer level in the vertical direction downward, showing a gradient distribution of grain size, thereby achieving a gradient grain distribution on the surface of the buffer layer material. The nanocrystalline surface can promote the migration of cathode spots to reduce the residence time of a single point, thereby improving the arc erosion resistance of the buffer layer.

[0044] Cyclic alternating deposition. Based on the layer A after roller pressing, the parameter combination is adjusted to perform secondary deposition manufacturing of the surface sub-functional layer B, such as Figure 2 As shown in d, the layer thickness and surface / internal forming quality are also focused on. Then, according to the number of layers contained in the specific electrode structure, the alternate deposition of layer A and layer B is performed in steps 2 to 4 for multiple iterations. Finally, after several cycles, a functional layer-substrate layered composite electrode blank is made, and the functional layer includes a preset stacked distribution sub-functional layer-buffer layer.

[0045] Post-processing: For the layered composite electrode blank prepared in steps 1 to 4, the outer peripheral wall and the upper surface are finely processed by CNC machining or other methods to remove surface defects such as burrs and spheroidized particles to ensure that the surface to be discharged is flat and smooth.

[0046] When designing the cathode material and configuration, the structural design scheme of the sub-functional layer and the buffer layer is shown in Figure 3. When the cathode arc discharge machining conditions are relatively normal, it is preferred to adopt a uniform thickness structure of the sub-functional layer and the buffer layer, such as Figure 3a When the single EDM time is long, the thickness of the sub-functional layer can be appropriately increased to ensure the stability of the machining process, such as Figure 3b Correspondingly, when the single EDM time is short and the current is large, in order to fully release the concentrated stress caused by the large current, the thickness of the buffer layer should be appropriately increased, such as Figure 3c shown.

[0047] The layered electrode with alternating sub-functional layers and buffer layers has uniform discharge ablation and anti-cracking mechanism. Figure 4 As shown in a. A refractory oxide layer is formed in situ on the surface of the sub-functional layer to protect the substrate and promote the high-speed movement of the cathode spot. The temperature of the cathode discharge part is high, and the temperature of the surrounding non-discharged parts is low. Thermal stress is formed under the influence of the temperature gradient, which in turn causes the cathode to bend and deform toward the center, as shown in Figure 4 As shown by the arrow a, thanks to the "soft-hard" combination of the multi-layer sub-functional layer and the buffer layer, the deformation is released layer by layer, thereby releasing the stress and reducing the tendency of cathode cracking. However, the layered cathode that is only strengthened by the surface coating is very easy to crack under concentrated stress, such as Figure 4 As shown in b, under the influence of bending stress, the surface strengthening layer and the substrate are torn and peeled off at the edge, and the interior also cracks longitudinally.

[0048] In this embodiment, the electrode is used for electrospark machining to prepare a diamond hole structure. The original layered electrode is a copper-chromium alloy electrode. The rod-shaped electrode is 20 cm long, the cross-section is diamond-shaped, and the diagonal lengths are 4 mm and 2 mm respectively. During use, the electrode discharges and burns violently, and even causes adjacent diamond holes to be damaged. In order to improve the service life of the electrode, a functional layer is designed on the surface of the original copper-chromium matrix. The interior of the functional layer is composed of a continuous and alternating zirconium-based sub-functional layer and a copper-chromium buffer layer in the vertical direction. During the cathode material and configuration design stage, considering that the hole making by electrospark machining occurs in an oxygen-containing atmosphere, it is necessary to enhance the air ablation resistance and uniform discharge performance of the cathode, so a thermochemical zirconium-based alloy is used as the sub-functional layer material. In order to alleviate the cracking and peeling of the functional layer caused by the high brittleness of zirconium oxide, a copper-chromium alloy with balanced strong plasticity is used as a buffer layer, assisted by surface rolling processing for surface grain nano-sizing. In terms of configuration design, the overall thickness of the functional layer is preset to 30 mm, the single layer thickness is 1.5 mm, and the thickness of a single zirconium-based alloy / copper-chromium alloy structure is 3 mm. Therefore, the overall functional layer contains 10 layers of zirconium-based alloy / copper-chromium alloy.

[0049] Copper-chromium base material deposition. A high-speed laser cladding system equipped with a dual powder barrel raw material feeding module was used to prepare the copper-chromium base layer. During deposition, the laser power was 3000W, the working distance was 15.5mm, the scanning rate was 6mm / s, and the cladding head reciprocated according to the preset trajectory. The closed area formed was a diamond with a diagonal length of 8mm and 4mm, so as to ensure the consistency of the thickness of the rod electrode surface edge and the internal deposition layer.

[0050] Grain gradient of copper-chromium surface layer by rolling. Based on the copper-chromium substrate prepared by deposition, the surface layer is pressed down by unidirectional rolling with a reduction of 0.5 mm, so that the copper-chromium surface is deformed into nanocrystalline.

[0051] Zirconium-based alloy and copper-chromium alloy are alternately clad and deposited. Zirconium-based alloy powder and copper-chromium alloy powder are loaded into two raw material feeding modules respectively. When depositing zirconium-based alloy, the laser power is 3500W, the working distance is 16.5mm, the scanning rate is 8mm / s, and the cladding head also reciprocates in the diamond area with a diagonal length of 8mm and 4mm according to the preset trajectory. After that, the copper-chromium buffer layer and the zirconium-based alloy functional layer are alternately deposited. When switching raw materials, the two raw material feeding modules are activated respectively, and argon is used as the powder carrier gas to transport it to the forming surface until the deposition of 10 layers of zirconium-based alloy / copper-chromium alloy on the surface of the copper-chromium substrate is completed.

[0052] Post-processing: The surface and peripheral contour of the layered composite cathode to be discharged are processed appropriately by high-speed milling to complete the preparation of the layered composite cathode.

[0053] Using a layered composite cathode with stacked functional layer / buffer layer, 40 diamond holes were processed by EDM. After the overall discharge time was about 15 minutes, the surface of the layered composite cathode was slightly blackened, and the strengthening layer structure was intact without obvious peeling or cracks. Observe the microscopic morphology of the discharge surface, such as Figure 5 As shown, the center of the zirconium-based alloy is concave, the burned area presents a nearly circular outline, and the cathode arc discharge and ablation are uniform, which confirms that the layered cathode based on the alternating distribution of functional layer / buffer layer has good crack resistance and arc ablation resistance.

[0054] Comparative Example 1

[0055] In this comparative example, the service scenario of the electrode is consistent with that of the embodiment. The specific difference is that only the process parameters are adjusted to prepare the zirconium-based alloy / copper-chromium alloy layered cathode, and the specific process adjustment method is to gradually increase the arc current from 20A to a preset value, so as to alleviate the cracking of the strengthening layer caused by the sudden increase in the current value.

[0056] The deposition of zirconium-based alloy on the surface of copper-chromium alloy also adopts high-speed laser cladding equipment with a laser power of 3000W, a working distance of 15.5mm, a scanning rate of 6mm / s, and a cladding head reciprocating along a preset trajectory.

[0057] The layered cathode was tested for hole making by EDM machining by increasing the arc current in a gradient manner. The discharge time was 15 minutes and the EDM machining of 40 diamond holes was completed. The surface of the layered cathode was obviously blackened, and cracks across the surface of the strengthening layer appeared in the middle. The cathode was severely burned. Further, the morphology of the burned surface was observed, such as Figure 6a As shown in the figure, transverse cracks are formed in the burnt area, and the strengthening layer is obviously peeled off ( Figure 6b ). After the cracks are formed, it is easy to induce the attachment of the arc root and concentrated discharge ablation, which aggravates the cathode failure. It can be seen that the cracking problem of the layered cathode cannot be effectively suppressed by process control alone.

Claims

1. A layered cathode structure based on alternating distribution of functional layer and buffer layer and a rapid trial production method thereof, characterized in that: The following steps are involved: Step 1: Cathode material and configuration design; select sub-functional layer and buffer layer materials according to the environmental characteristics of the cathode in the specific service process and the design criteria of special electrode materials; design the layer thickness and number of layers of the multi-layer composite structure with reference to the arc current and time of a single discharge machining; determine the preparation method of the multi-layer structure based on the material type and structural characteristics; Step 2: Deposition of substrate material; Metals A and B are used to represent the sub-functional layers and buffer layer materials of the layered electrode. On the surface of the conductive electrode substrate, the first layer A is melt-deposited based on reasonable manufacturing technology. The key control values ​​of the deposition process are layer thickness, surface and internal forming quality. Step 3: Grain gradient of surface layer by rolling: Based on the first layer A, the surface layer is pressed down by unidirectional rolling processing, so that the near-surface layer is deformed into a nanocrystalline and submicron crystalline deformation layer; after rolling processing, the grain size in the deformation layer gradually increases from the nanometer level to the micron level along the vertical direction downward, showing a gradient distribution of grain size, so as to achieve the surface grain gradient of the buffer layer material; Step 4: cyclic alternating deposition; based on the layer A after roller pressing, adjust the parameter combination to perform secondary deposition manufacturing of the surface sub-functional layer B, and also focus on controlling the layer thickness and surface / internal forming quality; then, according to the number of layers included in the specific electrode structure, iterate steps 2 to 4 for multiple times to perform alternating deposition of layer A and layer B, and finally after several cycles, a functional layer-matrix layered composite electrode blank is made, and the functional layer includes a preset stacked distribution sub-functional layer-buffer layer; Step 5, post-processing: For the layered composite electrode blank prepared in steps 1 to 4, the outer peripheral wall and the upper surface are finely processed by CNC machining to remove burrs and surface defects of spheroidized particles to ensure that the surface to be discharged is flat and smooth.

2. The layered cathode structure based on alternating distribution of functional layer and buffer layer and its rapid trial production method according to claim 1, characterized in that: The electrode material design criteria involved in the cathode material design stage are specifically centered around sub-functional layer materials and buffer layer materials; the sub-functional layer should have the following basic physical and chemical properties: 1) thermochemical discharge properties, with its own work function lower than 4.2eV, and at the same time, a conductive refractory oxide layer can be formed on the surface after discharge in an air atmosphere, and the oxide layer has stable performance and a melting point higher than that of pure metal; 2) the melting point is higher than that of the matrix material; 3) it has a certain plastic deformation ability; the buffer layer should have the following basic physical and chemical properties: 1) the plastic deformation ability is higher than that of the sub-functional layer material; 2) its own work function is not higher than 4.6eV; 3) when the linear expansion coefficient of the matrix is ​​X, the thermal expansion coefficient of the buffer layer is between 0.8X and 1.2X.

3. The layered cathode structure based on alternating distribution of functional layer and buffer layer and its rapid trial production method as claimed in claim 1 or 2, characterized in that: The functional layer involved in the layered cathode includes several sub-functional layers and a buffer layer, presenting a multi-layer stacked structure. The thickness of a single layer should be between 1 and 3 mm, and the overall functional layer thickness should not exceed 20 mm. In this way, the concentrated thermal stress of the functional layer during arc discharge is released layer by layer, alleviating the deformation mismatch caused by the mismatch in thermal expansion properties between the functional layer and the substrate.

4. The layered cathode structure based on alternating distribution of functional layer and buffer layer and its rapid trial production method as claimed in claim 1 or 2, characterized in that: The substrate material deposition process uses laser fuse deposition, high-speed laser cladding strong interface metallurgy combined with metal melting deposition technology. A parameter combination of high scanning rate and high laser power should be adopted in the deposition manufacturing process to increase the cooling rate of the molten pool and promote grain refinement.

5. The layered cathode structure based on alternating distribution of functional layer and buffer layer and its rapid trial production method as claimed in claim 3, characterized in that: The substrate material deposition process uses laser fuse deposition, high-speed laser cladding strong interface metallurgy combined with metal melting deposition technology. A parameter combination of high scanning rate and high laser power should be adopted in the deposition manufacturing process to increase the cooling rate of the molten pool and promote grain refinement.

6. The layered cathode structure based on alternating distribution of functional layer and buffer layer and the rapid trial production method thereof according to claim 1, 2 or 5, characterized in that: The buffer layer surface rolling grain gradient treatment is implemented in a way that a unidirectional rolling process is used to form a gradient grain size change from nanocrystalline to microcrystalline on the upper surface of the buffer layer; after processing, the upper surface of the buffer layer is nanocrystalline, and the grain size gradually increases from the surface to the inside to the micron scale.

7. The layered cathode structure based on alternating distribution of functional layer and buffer layer and the rapid trial production method thereof according to claim 1, 2 or 5, characterized in that: The anti-cracking property of the layered cathode structure with alternating functional layers and buffer layers is achieved through the design of a multi-metal layer stacking structure; the sub-functional layer directly faces the arc root, and it is difficult to avoid thermal stress during service. At this time, the buffer layer on the back will support the deformation of the sub-functional layer with a strong plastic deformation ability, thereby partially releasing the stress; After multiple sub-functional layers and buffer layers are compounded, the thermal stress of discharge ablation can be released to the greatest extent, deformation can be alleviated and interlayer cracking can be inhibited.

8. The layered cathode structure based on alternating distribution of functional layer and buffer layer and the rapid trial production method thereof according to claim 1, 2 or 5, characterized in that: The functional layer-buffer layer layered cathode structure has high uniformity and ablation resistance in the discharge ablation process; when the arc discharge continues, the sub-functional layer reacts in situ to generate a refractory oxide layer, which protects the substrate and reduces the ablation rate, while promoting the formation of type 1 cathode spots to improve ablation uniformity; when the single-layer functional layer is burned out, the buffer layer directly faces the arc root, and the surface nanocrystals can accelerate the migration of the cathode spots, reduce the residence time of the spots, and reduce the heat flux density on the cathode surface.

Citation Information

Patent Citations

  • Electrode structure with uniform and stable arcing characteristics and preparation technology thereof

    CN113056082A

  • Self-assembly AlCrNbSiTiN high-entropy alloy nitride nano multilayer composite coating for hard alloy blade and preparation method of self-assembly AlCrNbSiTiN high-entropy alloy nitride nano multilayer composite coating

    CN117026153A

  • Gradient titanium alloy additive manufacturing method based on interface in-situ nitriding strengthening

    CN118543849A

  • Amorphous diamond materials and associated methods for the use and manufacture thereof

    CN1836303A

  • Methods for laser-integrated additive manufacturing and connecting based on control of molten pool flow by pulsed laser

    WO2022127942A1

Cited By

  • Self-adaptive array type functional gradient electrode and manufacturing method thereof

    CN120920831A